The Influence of accountability and financial statements transparency on muzakki zakat paying consistency - Hasyim, Fuad; Nurjannah; Alfina Rahmatika (ASNAF : Journal of Economic Welfare, Philantrophy, Zakat and Waqf, 2022)
Objectives - This study aims to measure the effect of accountability and financial statements transparency on muzakki zakat paying consistency in Baitul Maal, Langsa City. Method - The data used in this study is primary data using a questionnaire distributed to muzakki who pay zakat in Baitul Maal, Langsa City. The analytical technique used in this research is multiple linear regression analysis. The research results show that the variables of accountability and transparency of financial statements partially affect the consistency of muzakki in paying zakat in Baitul Maal, Langsa City. The adjusted R Square value is 54.8%, which shows that the variable of accountability and transparency of financial statements can explain the variable consistency of muzakki paying zakat in Baitul Maal, Langsa City, by 54.8%. Limitations – This study has limitations regarding the relatively small number of research subjects. Practical Implications – As a practical implication, the results of this study can be used as a reference by the government, especially zakat institutions, in increasing the accountability and transparency of financial reports on the consistency of muzakki in paying zakat.